Early Time-Restricted Feeding Improves Insulin Sensitivity, Blood Pressure, and Oxidative Stress Even without Weight Loss in Men with Prediabetes - Sutton, Elizabeth F.; Beyl, Robbie; Early, Kate S.; Cefalu, William T.; Ravussin, Eric; Peterson, Courtney M. (Cell metabolism, 2018)
Intermittent fasting (IF) improves cardiometabolic health; however, it is unknown whether these effects are due solely to weight loss. We conducted the first supervised controlled feeding trial to test whether IF has benefits independent of weight loss by feeding participants enough food to maintain their weight. Our proof-of-concept study also constitutes the first trial of early time-restricted feeding (eTRF), a form of IF that involves eating early in the day to be in alignment with circadian rhythms in metabolism. Men with prediabetes were randomized to eTRF (6-hr feeding period, with dinner before 3 p.m.) or a control schedule (12-hr feeding period) for 5 weeks and later crossed over to the other schedule. eTRF improved insulin sensitivity, β cell responsiveness, blood pressure, oxidative stress, and appetite. We demonstrate for the first time in humans that eTRF improves some aspects of cardiometabolic health and that IF’s effects are not solely due to weight loss. [Display omitted] •Early time-restricted feeding (eTRF) increases insulin sensitivity•eTRF also improves β cell function and lowers blood pressure and oxidative stress•eTRF lowers the desire to eat in the evening, which may facilitate weight loss•Intermittent fasting can improve health even in the absence of weight loss Sutton et al. conduct the first supervised controlled feeding trial to test whether intermittent fasting has benefits in humans in the absence of weight loss. Prediabetic men following a form of intermittent fasting called early time-restricted feeding improved their insulin sensitivity, blood pressure, and oxidative stress levels without losing weight.